5,11,17,23-Tetra-tert-butyl-25,27-bis[2-(4-nitrophenoxy)ethoxy]calix[4]arene-26,28-diol acetonitrile tetrasolvate - Yuan, Jiu-Mao (International Union of Crystallography, 2009)
In the crystal structure of the title compound, C(60)H(70)N(2)O(10)·4CH(3)CN, the calix[4]arene molecule adopts an open-cone conformation with two intramolecular O—H⋯O hydrogen bonds. The four benzene rings of the calix[4]arene are twisted to the mean plane defined by four methylene C atoms bridging the benzene rings, with dihedral angles ranging from 57.74 (10) to 65.99 (12)°. Two pendant nitrophenyl rings are nearly perpendicular to each other, the dihedral angle being 70.9 (3)°. The asymmetric unit of the crystal structure contains four acetonitrile solvent molecules, one of which lies in the calix cavity and makes C—H⋯π interactions and another links with the calix[4]arene via C—H⋯O hydrogen bonding. One tert-butyl group is disordered over two sets of sites, with a 0.736 (13):0.264 (13) occupancy ratio.